ANALISIS KINERJA INSTALASI PENGOLAHAN AIR LIMBAH DOMESTIK STUDI KASUS PT. UNITED CAN Co. Ltd. - Nugroho, Rudi (Center for Environmental Technology, 2010)
Nowadays, the domestic wastewater have become a big problem in Indonesia especially in Jakarta. The governor of DKI Jakarta has established new regulation of domestic wastewater standard which can be discharge to the environment. The regulation namely Pergub 122 tahun 2005. To comply the regullation, PT. United Can Co. Ltd. has already built a domestic wastewater treatment using anaerobic-aerobic biofilter. The wastewater treatment has 130m3/day of treatment capacities. During the start-up periods till 3 months running, the compossition of influent and efluent were analysed weekly. The results show that the concentration of parameter of COD, BOD, TSS, Amonia, pH and MBAS in the effluent have bellow the limit noted in the Pergub 122 th 2005. Ã‚Â Keywords: Ã‚Â Domestic Wastewater, Biofilter, Anaerobic, Aerobic